IDEOLOGI PENDIDIKAN DALAM PENANAMAN NILAI KEISLAMAN DI MA DAARUL HIKMAH PAMULANG - Indrawati, Dewi; Jauza Adhawy, Hanifah; Rizki, Ananda; Azzahra, Fani; Ilham Riyadi, Ivan; Nurfattah Zahra, Ninda; Ramadhan, Renaldi (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2023)
This research was conducted at MA Daarul Hikmah Pamulang with the aim of knowing the Islamic values instilled in students and what educational ideology is applied at MA Daarul Himah Pamulang. The educational ideology applied can affect the educational process that takes place so that it can also affect the output / results of education. This research is a qualitative research by describing the problem in a descriptive narrative. Data collection is done by conducting observations, interviews, and documentation. Data analysis is done with qualitative analysis, while checking the validity of the data is done by conducting trigulation. The results of the study include: (1). Islamic values instilled in MA Daarul Hikmah Pamulang, namely: a. aqidah values, b. worship/sharia values, c. moral values. (2). Educational ideology used in instilling Islamic values at MA Daarul Hikmah Pamulang. MA Daarul Hikmah Pamulang in instilling Islamic values in students uses the ideology of conservatism education.